Danmark 1:200 000. Føroyar / Geodætisk institut (Geodætisk institut (Denmark), 1983)
Rættingar 1983 Relief shown by contours and spot heights. Depths shown by soundings.; Legend in Faroese, Danish, and English.; "Utgáva 3.5.1." Color; 1:200,000